The relationship between 25-hydroxyvitamin D, thyroid function and autoimmunity in the women at first trimester of pregnancy - Ferdos Zaman; Elham Bahramipour; Zahra Farhangiyan; Mozhgan Barati; Leila Moradi (Mashhad University of Medical Sciences, 2022)
Introduction: Hypovitaminosis D and thyroid disorders are associated with negative consequences during pregnancy. Regarding to the importance and prevalence of these two and the limited and contradictory information on their relationship, the present study was performed aimed to investigate the relationship between the level of 25-hydroxyvitamin D and thyroid function tests in the first trimester of pregnancy. Methods: This cross-sectional study was conducted in 2019 on 200 women in the first trimester of pregnancy.  Serum levels of 25 hydroxyvitamin D (to check vitamin D), total thyroxine (TT4), and thyroid-stimulating hormone (TSH) (to check thyroid function) and thyroid peroxidase (TPO) antibodies (to check autoimmunity) were measured.  Data were analyzed by SPSS statistical software (version 25) and Spearman's correlation coefficient and Kruskal-Wallis and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: There was no statistically significant difference in the mean level of TSH and T4 for different levels of vitamin D (p=0.272 and p=0.538, respectively), although in the group that were in the euthyroid range based on TSH (0.2 to  3.9 mg international units per liter), vitamin D level was significantly higher (p=0.013). A significant inverse relationship was found between deficient and insufficient levels of vitamin D with positive TPO antibody titer (p=0.034 and p=0.019, respectively). Conclusion: It seems that there is a relationship between vitamin D deficiency and thyroid autoimmunity, as well as between sufficient vitamin D levels and being in a euthyroid state, so it is suggested to correct vitamin D deficiency in women before attempting to pregnancy.